Analysis of intracranial hemorrhage grade in preterm singleton pregnancies delivered vaginally or by cesarean section - Ljuština Saša; Berisavac Ivana I.; Berisavac Milica; Kovačević-Vukolić Ljudmila; Veličković-Aleksić Vesna; Marković Nebojša (Vojnosanitetski Pregled, 2013)
Background/Aim. Preterm birth is the leading cause of neonatal mortality. Periventricular hemorrhage-intraventricular hemorrhage (PVH-IVH) remains a significant cause of both morbidity and mortality in infants prematurely born. The aim of the study was to evaluate the perinatal outcome regarding IVH of premature babies according to the mode of delivery. Methods. A total of 126 women in preterm singleton pregnancies with vertex presentation and 126 neonates weighted from 750 g to 1,500 g at birth were enrolled. The outcomes of 64 neonates born vaginally were compared to 62 neonates born by cesarean section. Results. There was no significant difference in the incidence of IVH among both groups. Conclusion. Our data is consistent with the hypothesis that the mode of delivery does not influence IVH and consenquently perinatal outcome in preterm neonates.